Comparative Distribution of Inheritance Assets Against Adopted Children Based on the Compilation of Islamic Law and Civil Law - Aulia, Febriana Putri; Kusriyah, Sri; Suwondo, Denny (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to examine and analyze the legal status of adopted children regarding the distribution of inheritance assets in terms of the Compilation of Islamic Law and Civil Law, as well as to analyze the responsibilities of Notaries in making wills for adopted children. The approach method used in this study is a normative juridical approach. The specifications of this study use descriptive analysis. The type of data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection method uses literature studies. The data analysis method used in this study uses qualitative analysis methods. The research results show that the distribution of inheritance to adopted children differs. This provision can be seen from the perspective of the Compilation of Islamic Law, as regulated in Article 209 of the Compilation of Islamic Law, which states that